Ionized vapor deposition of antimicrobial Ti–Cu films with controlled copper release; Thin Solid Films; Vol. 550 - Stranak V. Vitezslav; Wulff H. Harm; Ksirova P. Petra; Zietz C. Carmen; Drache S. Steffen; Cada M. Martin; Hubicka Z. Zdenek; Bader R. Rainer; Tichy M. Milan; Helm Ch. A. Christiane; Hipplera R. Rainer (2015, 2015)
Title screen